2010
DOI: 10.1007/s11908-009-0077-4
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-Infected Adolescent

Abstract: HIV-infected adolescents represent a unique, yet diverse, population requiring specialized medical and psychosocial HIV care. Perinatally infected and behaviorally infected adolescents often have differing therapeutic needs, but may share common difficulties, including medication nonadherence, high-risk sexual behavior, psychosocial stressors, and concomitant psychiatric disorders. Addressing these needs within a culturally sensitive framework and in the context of a population-specific approach to treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Earlier studies have reported that self-esteem and self-efficacy are linked with positive adaptation, promote psychological and social development in adolescents, and contribute to maximize their potential. However, fewer programs are formulated for screening and building intervention to enhance these variables [17][18][19].…”
Section: Ethical Considerationmentioning
confidence: 99%
“…Earlier studies have reported that self-esteem and self-efficacy are linked with positive adaptation, promote psychological and social development in adolescents, and contribute to maximize their potential. However, fewer programs are formulated for screening and building intervention to enhance these variables [17][18][19].…”
Section: Ethical Considerationmentioning
confidence: 99%
“…More than 25000 HIV-infected individuals aged 13-24 years old are currently undergoing the transition to adult outpatient care in the United States [61] . For this transition to be successful, the focus must fall on comprehensive care, including the patients' mental and reproductive health, gender identity, sexuality, stigmas, social issues, cognitive development, adherence to ART, detachment from pediatric outpatient care, and communication with the staff in charge of patient care [61][62][63] . Integral care poses a major challenge; however, it is crucial for the management of this population of patients to reduce the impact of the transition and improve their long-term follow-up.…”
Section: Transition To Adult Outpatient Carementioning
confidence: 99%
“…Integral care poses a major challenge; however, it is crucial for the management of this population of patients to reduce the impact of the transition and improve their long-term follow-up. Integral care is necessary to ensure that the therapeutic success achieved in childhood will continue during adulthood [60,62,64] .…”
Section: Transition To Adult Outpatient Carementioning
confidence: 99%
“…While there are a number of socio-structural determinants associated with poor health outcomes among ALWH [11][12][13][14], previous research has identified the transition from pediatric to adult care, frequently referred to as healthcare transition (HCT), as a particularly vulnerable period that influences health outcomes among ALWH [15][16][17][18][19][20][21]. HCT coincides with a time period during which many ALWH experience treatment interruptions and are at increased risk of loss-to-followup care (LTFU) only to return when critically ill [15]. In resource-limited settings, HCT often occurs at age 15 or younger, while in high-resource settings HCT occurs between ages 17 and 24 [16].…”
Section: Introductionmentioning
confidence: 99%